Mixed Triboelectric and Flexoelectric Charge Transfer at the Nanoscale. Issue 20 (13th August 2021) - Qiao, Huimin; Zhao, Pin; Kwon, Owoong; Sohn, Ahrum; Zhuo, Fangping; Lee, Dong‐Min; Sun, Changhyo; Seol, Daehee; Lee, Daesu; Kim, Sang‐Woo; Kim, Yunseok
Abstract: The triboelectric effect is a ubiquitous phenomenon in which the surfaces of two materials are easily charged during the contact‐separation process. Despite the widespread consequences and applications, the charging mechanisms are not sufficiently understood. Here, the authors report that, in the presence of a strain gradient, the charge transfer is a result of competition between flexoelectricity and triboelectricity, which could enhance charge transfer during triboelectric measurements when the charge transfers of both effects are in the same direction. When they are in the opposite directions, the direction and amount of charge transfer could be modulated by the competition between flexoelectric and triboelectric effects, which leads to a distinctive phenomenon, that is, the charge transfer is reversed with varying forces. The subsequent results on the electrical power output signals from the triboelectrification support the proposed mechanism. Therefore, the present study emphasizes the key role of the flexoelectric effect through experimental approaches, and suggests that both the amount and direction of charge transfer can be modulated by manipulating the mixed triboelectric and flexoelectric effects. This finding may provide important information on the triboelectric effect and can be further extended to serve as a guideline for material selection during a nanopatterned device design. Abstract : Using experimental approaches, the authors show that, in the presence of strain gradient, the charge transfer during triboelectric measurements is resulted from competition between flexoelectricity and triboelectricity. The charge transfer can be enhanced or inversed depending on the relative charge transfer direction of both effects. This finding could be a guideline for material selection for a nanopatterned device design.